Consciência sintática de crianças de 3º, 4º e 5º anos do ensino fundamental : instrumento de avaliação - Santos, Thaís Vargas dos (2017)
This research has as theme the syntactic awareness of students of 3rd, 4th and 5th grades of Elementary School. It has as main objective construct an instrument to evaluate the syntactic awareness of students of these levels of education and a manual for its use. It is theoretically supported on Psycholinguistics and its relations with Syntax, considering studies on the use and on the awareness in the use of ten syntactic cases selected. Methodologically, the syntactic awareness instrument of evaluation, with focus on these topics, uses four operational categories, three on the phrasal plane (identification task, judgment task, correction task) and a judgment task on the textual plane. The instrument elaboration process is developed through two steps. The first one involves the examination of materials and studies on syntactic awareness, the instrument first version construction, its application and the analysis of the results achieved with this pilot application with students of the stablished grades. The second step includes the instrument reworking based on the information obtained in the pilot situation, the elaboration of a manual for the instrument use and the application of the final version of the instrument with 12 students of the 3rd grade, 13 students of the 4th grade and 15 students of the 5th grade of elementary school. The results achieved are: the syntactic awareness instrument for the investigation of the 3rd, 4th and 5th grade of Elementary School; the application manual of the instrument constructed to guide professionals on the instrument use; the students' performance on the use of syntactic cases and the syntactic awareness of their use; the reconstitution of the syntactic awareness conception based on the research developed.